Conceptualizing patient-reported outcome measures for use within two Danish psychiatric clinical registries: description of an iterative co-creation process between patients and healthcare professionals. (18th August 2018) - Kristensen, S.; Mainz, J.; Baandrup, L.; Bonde, M.; Videbech, P.; Holmskov, J.; Bech, P.
Abstract: Background: Denmark has national clinical indicator programs for adult patients diagnosed with depression and schizophrenia, respectively. Within each program, the responsible steering group (SG) decided to add some indicators based upon patient-reported outcome measures (PROMs). Aims: The primary aim was to describe the process of selecting PROMs and defining a national measurement concept for use in clinical practice and for indicator monitoring and the secondary aim s to collect patient recommendations for implementation. Methods: An interdisciplinary SG of healthcare professionals and a Patient Peer Board (PPB) representing both patient groups co-created the output in an iterative process. The work included literature search, PPB workshops, SG meetings, ratings of PROM topics and items, and a pilot. The PPB discussed the following: item relevance, mode of data collection, graphical format of the online PROMs, and display of results. Finally, requirements for PROM patient information were identified. Based upon input from the PPB, the SG selected the items and specified the measurement concept. Results: The PPB prioritized 20 of 53 suitable items and suggested alternative wording and answer categories. A pilot was performed and 19 items covering well-being, lack of well-being, impairment of functioning, and overall health were selected for clinical testing. The patients recommended concrete, unambiguous, easily understandable information and procedures for data collection and display of results. Conclusions: The iterative co-creation process based upon a high degree of patient involvement resulted in a set of PROMs, a national measurement concept, and patient recommendations for implementation. The cooperation between patients and professionals was successful.